(untitled) (International Journal of Nursing Education, 2022)
The importance of service as an added value different between organizations and improving customer conservation has motivated organizations to adopt models and instruments to improve service and enhance customer satisfaction. Based on the premise that “managing means assessing”, organizations have been investing in various tools aimed at assessing service, detecting service gaps, and identifying the central elements that affect customer satisfaction. The study characterized and compared two central tools for assessing satisfaction: the SERVICEQUAL model, which examines the gaps in service in five different dimensions, and the PS3 model, which examines the effect of three elements—Personal care, Physical surrounding, and Process technical—on women’s satisfaction with childbirth care. The findings show that in both models, the dimension of personal touch, particularly empathy, accessibility, and reliability of the medical team, was the most meaningful parameter in determining the level of satisfaction and the service experience of the mother. Additionally, according to the SQ model, the tangibles of the service also carry an important role in the patient’s satisfaction during childbirth. In other words, better service in terms of the tangible elements of the process lead to higher satisfaction among the patients.